Equal Employment Opportunity in Indonesia: Antecedent of Human Resources Management Practices and Service Performance of Government Employees in Tanjungpinang - Wayu Eko Yudiatmaja (Jurnal Borneo Administrator: Media Pengembangan Paradigma dan Gaya Baru Manajemen Pemerintahan Daerah, 2020)
Recently, government employees encountered issues of service performance because of the rising citizen’s demand to get a better service quality. The concern of the researchers to relate employee service performance with equal employment opportunities and the practices of human resource management still limited. Using social exchange theory, recemt study aims to examine the relationship between equal employment opportunity and employee service performance in the public sector. This research also investigates the mediating role of human resource management practices between the equal employment opportunity and employee service performance. This study was conducted among public servants in Tanjungpinang. A total of 258 public servants responded to the survey. The data were analyzed using structured equation modeling. The findings showed a positive relationship between equal employment opportunity and service performance. Besides, this study also claimed that human resource management practices mediate the connection between equal employment opportunity and service performance. The research implications and future research area need further elaboration.